Stock Assessment using a Cash Equivalent Based on Sourcing Management - Jebur, Shatha abdul hussein; Jody al-duleimy, Haidar hamza (ExcelingTech, 2019)
Abstract— The current research aims to use the Merrett and Newbould stock equivalent cash model which was developed 1982 to evaluate the shares of listed companies in the stock market. It developed based on the source management by measuring the real value of the shares and using the equivalent cash-share model of the EPS per share instead of the profit dividend for one side that is taking the retained earnings into consideration. The data analysis relied on a set of statistical methods to achieve its objectives and test the validity of its hypotheses, including the standard deviation, the simple linear regression model, the selection coefficient (R2) and T-test for testing research hypotheses. Data have been analysed to extract results using the statistical software called SPSS program, while the Iraq Stock Exchange was selected as a population of the study, and the banking sector was selected as a research sample because it is the most active as compare to other sectors during the period of study (2014 -2017) according to the data published in the directory of the Iraqi stock exchange. The present research reached a number of conclusions, and concluded that it is not possible to apply the equivalent monetary model in the Iraqi financial market, and this is what the real values of the shares calculated according to the model used for current study.